Greater sage‐grouse respond positively to intensive post‐fire restoration treatments - Poessel, Sharon A.; Barnard, David M.; Applestein, Cara; Germino, Matthew J.; Ellsworth, Ethan A.; Major, Don; Moser, Ann; Katzner, Todd E. (Ecology and evolution, 2022)
Habitat loss is the most prevalent threat to biodiversity in North America. One of the most threatened landscapes in the United States is the sagebrush (Artemisia spp.) ecosystem, much of which has been fragmented or converted to non‐native grasslands via the cheatgrass‐fire cycle. Like many sagebrush obligates, greater sage‐grouse (Centrocercus urophasianus) depend upon sagebrush for food and cover and are affected by changes to this ecosystem. We investigated habitat selection by 28 male greater sage‐grouse during each of 3 years after a 113,000‐ha wildfire in a sagebrush steppe ecosystem in Idaho and Oregon. During the study period, seeding and herbicide treatments were applied for habitat restoration. We evaluated sage‐grouse responses to vegetation and post‐fire restoration treatments. Throughout the 3 years post‐fire, sage‐grouse avoided areas with high exotic annual grass cover but selected strongly for recovering sagebrush and moderately strongly for perennial grasses. By the third year post‐fire, they preferred high‐density sagebrush, especially in winter when sagebrush is the primary component of the sage‐grouse diet. Sage‐grouse preferred forb habitat immediately post‐fire, especially in summer, but this selection preference was less strong in later years. They also selected areas that were intensively treated with herbicide and seeded with sagebrush, grasses, and forbs, although these responses varied with time since treatment. Wildfire can have severe consequences for sagebrush‐obligate species due to loss of large sagebrush plants used for food and for protection from predators and thermal extremes. Our results show that management efforts, including herbicide application and seeding of plants, directed at controlling exotic annual grasses after a wildfire can positively affect habitat selection by sage‐grouse. We investigated habitat selection by 28 male greater sage‐grouse during each of 3 years after a wildfire in Idaho and Oregon. Sage‐grouse avoided areas with high exotic annual grass cover but selected for recovering sagebrush, areas that were intensively treated with herbicide, and areas that were seeded with sagebrush, grasses, and forbs. Our results show that management efforts directed at controlling exotic annual grasses after a wildfire can positively affect habitat selection by sage‐grouse.